The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1103/physreve.86.025101
|View full text |Cite
|
Sign up to set email alerts
|

Onset of localization in heterogeneous interfacial failure

Abstract: We study numerically the failure of an interface joining two elastic materials under load using a fiber bundle model connected to an elastic half space. We find that the breakdown process follows the equal load sharing fiber bundle model without any detectable spatial correlations between the positions of the failing fibers until localization sets in. Depending on the elastic constant describing the elastic half space, localization sets in before or after the critical load causing the interface to fail complet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 24 publications
2
31
2
Order By: Relevance
“…Hence, changing e without changing k is equivalent to changing L-and hence the linear size of the system-while keeping the elastic properties of the system constant [32]. This is a central point in what follows.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Hence, changing e without changing k is equivalent to changing L-and hence the linear size of the system-while keeping the elastic properties of the system constant [32]. This is a central point in what follows.…”
Section: Model and Methodsmentioning
confidence: 99%
“…When the distances are measured in units of the discretization size dl, the relative influence of the elastic interactions with respect to the global loading has been found to be described by a single parameter named the reduced Young modulus [35] e = Edl N .…”
Section: Modelmentioning
confidence: 99%
“…Completely ductile failure gives a b-value of 0.63, while for brittle fractures, b = 1.2. A recently developed bottom-up model of fracture by Stormo et al (2013) has shown to have similar diffuse to localized damage distribution transition. This model can address the competition between elastic stress redistribution and damage development related to geological heterogeneity.…”
Section: Introductionmentioning
confidence: 98%
“…This model can address the competition between elastic stress redistribution and damage development related to geological heterogeneity. Here, we refine and expand the model proposed by Stormo et al (2013) with the attempt to describe fracture development along a pre-existing weak interface. We observe in our model a similar effective ductile to brittle transition at large scale as observed by previous authors.…”
Section: Introductionmentioning
confidence: 99%